FoodShare Participation and Household Economic Vulnerability in Wisconsin Counties, 2019–2023 - Cheng, Sizhe (Exploring Science Academic Conference Series, 2026)
This study examines annual FoodShare recipient rates in 71 Wisconsin counties in 2019, 2021, 2022, and 2023, with particular attention to households below the poverty line and households classified as ALICE (Asset Limited, Income Constrained, Employed). FoodShare participation is used as a county-level proxy for food-assistance use and food-insecurity risk rather than as a direct measure of food insecurity. Combining data from the Wisconsin Department of Health Services, the U.S. Census Bureau/American Community Survey, and the United for ALICE Research Center, the analysis shows that the mean county FoodShare recipient rate was higher in 2021, the first observed pandemic-era year in the dataset, than in 2019, and it remained above the 2019 baseline in 2023. Regression results indicate that both poverty-household rates and ALICE-household rates are positively associated with FoodShare participation in cross-county models. Robustness checks show that these relationships remain present in population-weighted models and when Milwaukee County is excluded, while county fixed-effects models suggest that much of the relationship reflects persistent differences across counties rather than short-run within-county changes. The findings support a broader interpretation of household economic vulnerability: poverty measures identify severe hardship, while ALICE measures capture additional households above the federal poverty line but below the basic cost of living in their county.